Intestinal Microbiota Influence Immune Tolerance Post Allogeneic Hematopoietic Cell Transplantation and Intestinal GVHD - Köhler, Natalie; Zeiser, Robert (Frontiers in Immunology, 2019)
Under normal conditions our intestines are inhabited by trillions of diverse microorganisms composing the intestinal microbiota, which are mostly non-pathogenic anaerobic commensal bacteria vital for the maintenance of immune homeostasis. The composition and diversity of the intestinal microbiota can be disturbed by various factors including diet, antibiotics and exposure to intestinal pathogens. Alterations of the intestinal microbiota contributes to many diseases including graft-versus-host disease (GVHD), a life threatening complication that occurs after allogeneic hematopoietic cell transplantation (allo-HCT) caused by an allogeneic reaction of donor T cells against recipient target tissues. Intestinal GVHD is most difficult to treat and connected to a high mortality. Due to recent advances in high-throughput sequencing technology, composition of the microbiome during allo-HCT has been characterized and some common patterns have been identified. Metabolites produced by intestinal bacteria were shown to promote intestinal tissue homeostasis and immune tolerance post allo-HCT. In this review, we discuss the role of the intestinal microbiota and metabolites in the context of acute GVHD. Moreover, novel therapeutic approaches that aim at protecting or regenerating intestinal cell populations will be highlighted.